Dynamics of Simian Immunodeficiency Virus Two-Long-Terminal-Repeat Circles in the Presence and Absence of CD8(+) Cells - Policicchio, Benjamin B. (J Virol, 2018)
CD8(+) cells play a key role in human immunodeficiency virus (HIV)/simian immunodeficiency virus (SIV) infection, but their specific mechanism(s) of action in controlling the virus is unclear. Two-long-terminal-repeat (2-LTR) circles are extrachromosomal products generated upon failed integration of HIV/SIV. To understand the specific effects of CD8(+) cells on infected cells, we analyzed the dynamics of 2-LTR circles in SIVmac251-infected rhesus macaques (RMs) treated with an integrase inhibitor (INT). Twenty RMs underwent CD8(+) cell depletion and received raltegravir (RAL) monotherapy or a combination of both. Blood, lymph nodes (LNs), and gut biopsy specimens were routinely sampled. Plasma viral loads (pVLs) and 2-LTR circles from peripheral blood mononuclear cells (PBMCs) and LN lymphocytes were measured with quantitative reverse transcription-PCR (qRT-PCR). In the CD8 depletion group, an ∼1-log increase in pVLs and a slow increase in PBMC 2-LTRs occurred following depletion. In the INT group, a strong decline in pVLs upon treatment initiation and no change in 2-LTR levels were observed. In the INT and CD8(+) cell depletion group, an increase in pVLs following CD8 depletion similar to that in the CD8 depletion group was observed, with a modest decline following INT initiation, and 2-LTR circles significantly increased in PBMCs and LNs. Analyzing the 2-LTR data across all treatment groups with a mathematical model indicates that the data best support an effect of CD8(+) cells in killing cells prior to viral integration. Sensitivity analyses of these results confirm that effect but also allow for additional effects, which the data do not discriminate well. Overall, we show that INT does not significantly increase the levels of 2-LTR circles. However, CD8(+) cell depletion increases the 2-LTR levels, which are enhanced in the presence of an INT. IMPORTANCE CD8(+) T cells play an essential role in controlling HIV and SIV infection, but the specific mechanisms involved remain poorly understood. Due to failed viral infection, HIV and SIV can form 2-LTR extrachromosomal circles that can be quantified. We present novel data on the dynamics of these 2-LTR forms in a SIV-infected macaque model under three different treatment conditions: depletion of CD8(+) cells, administration of the integrase inhibitor in a monotherapy, which favors the formation of 2-LTR circles, and a combination of the two treatments. We used a new mathematical model to help interpret the data, and the results suggest that CD8(+) cells exert a killing effect on infected cells prior to virus integration. These results provide new insights into the mechanisms of action of CD8(+) cells in SIV infection. Confirmation of our results would be an important step in understanding immune control of HIV.